Voszmozhnosti finansirovaniya sporta za schyet igornogo biznesa - Zolotov, M. I.; Kuzin, V. V.; Kutepov, M. E. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
To analysis of the opportunities in Sport`s Financing by Gambling Business is the aim of this paper. The authors describe the Finish experience of the Gambling Business`es use to support the national sport`s development. The consider the activization of the legislative-creative activities as well as the activities for elaboration of sub-law deeds will allow to conclude the forming of the normative documents` completion, regulating the gambling business and the lotteries realization in Russian Federation. It will contribute to actualize the opportunity to finance the sport`s development in Russia by the gambling business and lotteries.